2010
DOI: 10.1038/cmi.2010.56
|View full text |Cite
|
Sign up to set email alerts
|

A reversed CD4/CD8 ratio of tumor-infiltrating lymphocytes and a high percentage of CD4+FOXP3+ regulatory T cells are significantly associated with clinical outcome in squamous cell carcinoma of the cervix

Abstract: In this study, 40 biopsy samples collected from cervical cancer patients at the First Affiliated Hospital of Xi'an Jiaotong University, China, were retrospectively assessed using immunohistochemistry for CD4 1 and CD8 1 tumor-infiltrating lymphocytes (TILs) and were analyzed for the expression of FOXP3, OX40, granzyme B (GrB) and perforin (Prf). The proliferating index of the TILs was determined by assessing Ki67 expression. We determined the prognostic value of low and high numbers of TILs on survival by perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(178 citation statements)
references
References 51 publications
(56 reference statements)
9
168
0
1
Order By: Relevance
“…Thus, the development of an immune response mediated by CD4 ϩ Th1 lymphocytes has been associated with regression of ano-genital warts (21). In addition, the increased frequency of cervical cancer in patients with altered CD4 ϩ cells highlights the importance of this cell population in the control of HPV infection (23).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the development of an immune response mediated by CD4 ϩ Th1 lymphocytes has been associated with regression of ano-genital warts (21). In addition, the increased frequency of cervical cancer in patients with altered CD4 ϩ cells highlights the importance of this cell population in the control of HPV infection (23).…”
Section: Discussionmentioning
confidence: 99%
“…Shah and colleagues used 2-color IHC to identify both CD4þFoxP3þ and CD8þFoxP3þ T cells in cervical cancer. Intriguingly, they found CD8þFoxP3þ T cells at a mean number of 3.32 per high-power field and CD4þFoxP3þ T cells at a mean number of 11.45 per high-power field (30). Thus, had they used FoxP3 as a single marker, only $75% of the cells they measured would have been CD4þ T cells, which underscores the fact that not all FoxP3þ T cells are conventional Tregs.…”
Section: Use Of Multiple Markers To Define Foxp3þ T Cellsmentioning
confidence: 97%
“…In the end, we reviewed 58 studies encompassing 16 different cancer types (Table 1), including bladder (19), breast (21)(22)(23)(24)(25)(26)(27)(28), cervical (29,30), colorectal (12,(31)(32)(33)(34)(35)(36)(37)(38)(39), endometrial (40)(41)(42), gastric (14,(43)(44)(45)(46), head and neck (47), hepatocellular (48)(49)(50)(51)(52), lung (53,54), melanoma (55)(56)(57)(58), mesothelial (59), oral (4,(60)(61)(62)(63), ovarian (2,3,…”
Section: Introductionmentioning
confidence: 99%
“…9 These observations suggest that the success of immunotherapy for cancer may ultimately depend on the balance between Treg and Teff cells. 10,11 Increasing evidence indicates that Tregs mediate immunosuppressive functions through the utilization of many soluble mediators and cell-to-cell contact, further inducing a positive feedback loop. 1 Bopp et al 12 showed that natural Tregs can transfer cyclic adenosine monophosphate (cAMP) to Teff cells, resulting in increased intracellular cAMP concentrations in Teff cells.…”
Section: Introductionmentioning
confidence: 99%